Efektifitas Pemanfaatan Sumur Resapan dan Biopori sebagai Artificial Recharge untuk Meresapkan Air Hujan ke dalam Lapisan Akuifer Dangkal pada DAS Batang Kuranji Kota Padang - Alviansyah Alviansyah; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. The population density in Batang Kuranji wathershed caused land clearing to build new settlement areas. However, this land clearing caused a new problem; causing a reduction of green areas that function as rainwater catchment areas. It also can cause an area to have the potential for flooding. Furthermore, it can decrease the quantity of groundwater. In order to increase the effort to absorb rainwater into the soil in Batang Kuranji watershed, so that the artificial recharge was carried out. The method used was the construction of absorption wells and biopores. This research was conducted to calculate the volume of rainwater that can be absorbed by absorption wells and biopores in certain rainy conditions in Batang Kuranji watershed. Besides that, hydraulic conductivity testing was carried out in order to know how the state of the soil texture in the study area. This study used an experimental method that was carried out in Batang Kuranji watershed, Padang City. Based on the insitu soil hydraulic conductivity test, the average hydraulic conductivity value in the absorption wells area was 1.925 x 10-3 cm/second. This value described that the soil in the study area was classified as a relatively fast soil classification in absorbing water. After conducting the research with three measurements, it was found that the total water discharge absorbed by the gutter water absorption wells was 0,215 m 3 , for open absorption wells was 0,222 m 3 , and for biopores was 0,0104 m 3 .Keywords: Artificial Recharge, Absorption Wells, Biopores, Hydraulic Conductivity